Kolaborasi Bidan dan Bidan Kampung pada Masyarakat Dayak Siang-Murung: Sebuah Etnografi Kesehatan Ibu dan Anak - Rachmalina Soerachman; Setia Pranata; M. Gullit Agung; Salahudin Muhidin (Antropologi Indonesia, 2020)
This ethnographic study focuses on the Dayak Siang-Murung community in Dirung Bakung village, Central Kalimantan, in their efforts to reach a better health development, especially in maternal and neonatal health. Considering different perceptions about traditional and professional midwives within the community, this study attempts to identify challenges and possible solutions to reach the health development goal in this region. An ethnographic design was conducted by interviewing several informants, including traditional midwives (bidan kampung), professional midwives (bidan desa), expectant mothers, and village leaders, regarding their perceptions and experiences in dealing with the issues and practices of maternal and newborn health in the village. The findings show that the majority of Dayak Siang-Murung community preferred to seek health cares, especially related to maternal and newborn health cares, from traditional healers rather than from professional midwives. This is mainly influenced by relatively low levels of mothers’ trust in the health care system and their choice of healthcare workers. With the spirit of ‘Tira Tangka Balang’ (commit to work and reach the ultimate goals), a collaboration was encouraged between the traditional and professional midwives, especially during home visitation and delivery process, to improve the health condition of the Dayak Siang-Murung community.